2023
DOI: 10.1001/jamanetworkopen.2023.16545
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Gun Violence Archive as an Epidemiologic Data Source for Community Firearm Violence in 4 US Cities

Abstract: ImportanceFirearm injury is a major public health burden in the US, and yet there is no single, validated national data source to study community firearm violence, including firearm homicide and nonfatal shootings that result from interpersonal violence.ObjectiveTo assess the validity of the Gun Violence Archive as a source of data on events of community firearm violence and to examine the characteristics of individuals injured in shootings.Design, Setting, and ParticipantsThis cross-sectional observational st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In particular, fatal shootings and incidents involving children were found to have a high capture rate when compared to police data. However, those findings were based on 4 urban areas; therefore, results may differ for other geographic areas (Gobaud et al 2023 ). The findings of this report are subject to at least 6 limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, fatal shootings and incidents involving children were found to have a high capture rate when compared to police data. However, those findings were based on 4 urban areas; therefore, results may differ for other geographic areas (Gobaud et al 2023 ). The findings of this report are subject to at least 6 limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Third, since the GVA is not 100% complete in the reporting of unintentional firearm injury deaths, we could not establish a true mortality rate. Fourth, the GVA capture rate may be impacted by external influences on news media coverage (Gobaud et al 2023 ). Factors such as politics, advocacy, and news media goals may increase or decrease reporting in shooting events.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, though there have been few comprehensive studies conducted to confirm the reliability, reproducibility, or validity of the GVA database, a recent study by Gobaud et al revealed that the GVA is generally an appropriate model for firearm violence research. Despite these limitations, the GVA is one of the most comprehensive databases on this topic that has been utilized in numerous studies and by news sources [ 3 , [27] , [28] , [29] , [30] ]. Furthermore, the methods of collection by the GVA have changed over time and vary depending on the location (e.g., increased coverage of urban compared to rural locations).…”
Section: Discussionmentioning
confidence: 99%
“…GVA data are typically used to measure intentional, interpersonal firearm violence, because intentional self-harm incidents (ie, suicides and suicide attempts) are omitted and unintentional shootings are a small proportion of total incidents. Validation work has found good sensitivity (81%) and excellent specificity (99%) when comparing the GVA with incident-level firearm violence data compiled by local police agencies, which are considered the criterion standard . We geocoded the GVA location data to US counties and analyzed a combined total count of fatal and nonfatal shootings from 2014 to 2019.…”
Section: Methodsmentioning
confidence: 99%
“…Validation work has found good sensitivity (81%) and excellent specificity (99%) when comparing the GVA with incident-level firearm violence data compiled by local police agencies, which are considered the criterion standard. 34 We geocoded the GVA location data to US counties and analyzed a combined total count of fatal and nonfatal shootings from 2014 to 2019. For both outcomes (NCHS firearm-related mortality and GVA combined fatal and nonfatal shootings), we estimated a quarterly, county-level rate using the annual county population provided by the US Bureau of the Census County Population Estimates (2014-2019).…”
Section: Methodsmentioning
confidence: 99%